تقييم الأداء الوظيفي للشبكة الطرقية في الحي السكني بالاعتماد على بنيتها (مدينة حمص مثالاً) - رشيد, ميسون (Latakia University Journal -Engineering Sciences Series, 2016)
أجري هذا البحث على مدينة حمص–سورية كحالة دراسية، بهدف دراسة بنية شبكة الطرق،والجدال الدائر حول أكفأ الشبكات وظيفياً,تلك التي تميل للنمط الشبكيgrid)) أم التي تميل للنمط الشجري (tree) أم أنماط أخرى،وللقيام بذلك تم التركيز على مبادئ الأداء الوظيفي لشبكة الطرق والتي يمكن تلخيصها بالتالي: (التقاربية – النفاذية – الأمان). والعمل على تحديد مؤشرات الأداء الوظيفي المشتقة منها، وطرق قياسها، وكانت هذه المؤشرات (نسبة عدد الخلايا إلى عدد النهايات المغلقة {Cell / Cul ratio} -عدد التقاطعات الثلاثية إلى الرباعية {{T / X ratio– المسافة بين المركز والأطراف – عدد الخلايا في وحدة المساحة-الهرمية). تم تطبيق مؤشرات الأداء الوظيفي على حالات الدراسة (الأحياء المنظمة والضواحي السكنية).وتبين أن شبكة الطرق يجب أن تتمتع بتقاربية ونفاذية متوسطة لشبكة الطرق، وعالية لشبكة المشاة. لذلك فإن أنماط الشبكات المرشحة لتكون أكفأ وظيفياً هي التي تحمل سمات النمطين الشبكي والشجري بشرط أن يؤخذ مبدأ الأمان بعين الاعتبار.This research has been implemented in Homs city-Syria, in order to study the configuration of the road network in residential district, and the debates about the most efficient pattern in terms of f¬¬¬unctional performance, treeor grid pattern, or other patterns. In order to do that, it focused on the planning principles of functional performance, which can be summarized to:( proximity, permeability, security). And worked on identifying Accurately the functional performance indicators, and there measuring method, and they were (Cell / Cul ratio – T / X ratio- distant between the center and the periphery - number of cells per unit area –hierarchy). And applied it on the case studies: (organized / newly planned residential districts). It turns out that the road network should have a medium proximity and permeability for traffic,while it should be high for pedestrian. Therefore,the network patternCandidate forbetterfunctional performance when it's nearly in the mid-way between (tree and grid).